MANGO: low-cost open source needle guidance - Galvão da Mata J.V.; Krumb H.; Mishra U.; Mukhopadhyay A.; Essert C. (My University, 2025)
Validating experiments in intra-operative planning for percutaneous interventions requires to localise the needle with a tracking system. As commercial optical trackers are expensive, we present MANGO, a low-cost OpenSource solution for needle tracking. We first present the design of our system, which localises coloured orbs using a stereo-camera setup. Based on this setup, we investigate the static and dynamic error of the system, and experiment with signal filtering to improve tracking performance. With the MANGO, we are able to meet the positional accuracy margin of 5 mm usually required in percutaneous interventions. Orientational accuracy, measured by needle tip localisation accuracy as a proxy measure, exceeds this margin. We plan to investigate this further in future research. Releasing our code, data and 3D models, we aim to provide a low-cost and reproducible platform for needle tracking and validation of intra-operative planning in research environments. © 2022 Informa UK Limited, trading as Taylor & Francis Group.